2008
DOI: 10.1111/j.1471-4159.2008.05341.x
|View full text |Cite
|
Sign up to set email alerts
|

Androgens regulate neprilysin expression: role in reducing β‐amyloid levels

Abstract: Age‐related testosterone depletion in men is a risk factor for Alzheimer’s disease. Prior studies suggest that androgens affect Alzheimer’s disease risk by regulating accumulation of β‐amyloid protein (Aβ) by an undefined mechanism. In this study, we investigated the role of the Aβ‐catabolizing enzyme neprilysin (NEP) in this process. First, we observed that androgens positively regulate neural expression of NEP in adult male rats. Next, we investigated androgen regulatory effects on both NEP expression and Aβ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 67 publications
6
60
0
Order By: Relevance
“…Because the injection of testosterone has been shown to reduce deposits of β-amyloid protein in vitro through the enhanced effects of neprilysin (42), it might be that mild exercise, in mediating paracrine effects through androgens and/or DHT, may, in turn, also reduce the deposits of β-amyloid protein and protect cognitive functions.…”
Section: Discussionmentioning
confidence: 99%
“…Because the injection of testosterone has been shown to reduce deposits of β-amyloid protein in vitro through the enhanced effects of neprilysin (42), it might be that mild exercise, in mediating paracrine effects through androgens and/or DHT, may, in turn, also reduce the deposits of β-amyloid protein and protect cognitive functions.…”
Section: Discussionmentioning
confidence: 99%
“…Last year, Yao et al (37) found that androgen up-regulates neprilysin gene expression, and their study suggests that androgen treatment could reduce accumulation of A␤, as a therapeutic approach for AD. This study demonstrates positive regulation of neprilysin expression by 17␤-estradiol, leading to A␤ degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Testosterone was found to downregulate β-secretase to reduce Aβ accumulation [69] by upregulating neprilysin, a primary protease involved in the regulation of Aβ breakdown [70]. Another study reported that testosterone reduced the Aβ accumulation by offsetting the age-related decline in neprilysin expression [71]. Decreased levels of testosterone result in an increased risk for the development of AD in men since it also acts as an endogenous regulator of Aβ [72].…”
Section: Endocrinal Dysregulations In the Ad Pathophysiologymentioning
confidence: 99%